THE SHARE OF BARK IN ENERGY CHIPS FROM SHORT ROTATION COPPICE OF POPLARS AND WILLOWS GROWN ON PLANTATIONS (Innovation in Woodworking Industry and Engineering design, 2026)
In this contribution, the results of experimental works assessing the share of bark in energy chips of selected clones of short rotation coppice of Salix viminalis and poplars with 5-year harvesting cycle, grown in the region of Slovakia and Moravia, are shown. Energy chips made of dendromass from fast growing trees grown on plantations is a bio-fuel consisting of juvenile wood and juvenile bark. The share of bark in energy chips influences the environmental properties and ash content of a bio-fuel. The share of bark in energy chips from clones RAPP, OLM, ULV and Inger of Salix viminalis in bio-fuel is XB = 16,8 ÷ 19,7 % and the share of bark in chips from clones Max5, Oxford, AF2 a Monviso of poplars grown on plantations is XB = 20,97 ÷ 26,67 %.